A sentimental Christmas with Nat "King" Cole and friends [compact disc] : Cole classics reimagined - Cole, Nat King, 1919-1965; Mathis, Johnny; Chenoweth, Kristin; Scott, Calum; Estefan, Gloria; Legend, John (Capitol, 2021)
"The new album 'A Sentimental Christmas with Nat King Cole and Friends: Cole Classics Reimagined' weaves Nat's unparalleled, beautifully restored vocals with new arrangements and contemporary artists creating beautiful sentimental duets of holiday classics"--Amazon.com.